The Role of Four-Wheel Patrols by the Turjawali Unit of the Sabhara Unit of the Garut Police in Preventing Motor Vehicle Theft in the Jurisdiction of the Garut Police - Zakiy, Abid Naufal (Indonesian Journal of Police Studies, 2024)
The high number of criminal acts of vehicle theft (Curanmor) is the background of this research. Gave rise to a criminal action is resulting in the dynamics of the community. This created an impression in the role of four wheeled patrol by Unit Turjawali Satuan Sabhara Garut Resort Police . The purpose of this research is describe the role of four-wheeled patrol by Unit Turjawali Satuan Sabhra Garut Police Resort, know factors influencing on the role of four-wheeled patrol, and knows efforts to enhance the role of four-wheeled patrol by Unit Turjawali Satuan Sabhara Garut Resort Police. Research focus is four-wheeled patrol by Unit Turjawali Satuan Sabhara Garut Resort Police. The research uses a qualitative approach through a method of descriptive analysis .Analysis using the concept of the role, the concept of patrol, the concept of vehicle theft, management functions theory, management elements theory, and social crime prevention theory in clarifying the problems that obtained. The findings of the research that remains to be seen the role of four-wheeled patrol by Unit Turjawali Satuan Sabhara Garut Resort Police in preventing criminal action see some aspects that have not fully be done in accordance with applicable regulations. Factors influencing the is support as infrastructure available in good condition. The factors hindering as a lack of human resources in quality and quantity. In addition to routine of four-wheeled patrol, efforts have been made by adding personnel at certain points having high sensitivity level.